Manipulation of salicylate content in Arabidopsis thaliana by the expression of an engineered bacterial salicylate synthase - Mauch, Felix; Mauch-Mani, Brigitte; Gaille, Catherine; Kull, Beatriz; Haas, Dieter; Reimmann, Cornelia (My University, 2001)
Salicylic acid (SA) plays a central role as a signalling molecule involved in plant defense against microbial attack. Genetic manipulation of SA biosynthesis may therefore help to generate plants that are more disease-resistant. By fusing the two bacterial genes pchA and pchB from Pseudomonas aeruginosa, which encode isochorismate synthase and isochorismate pyruvate-lyase, respectively, we have engineered a novel hybrid enzyme with salicylate synthase (SAS) activity. The pchB-A fusion was expressed in Arabidopsis thaliana under the control of the constitutive cauliflower mosaic virus (CaMV) 35S promoter, with targeting of the gene product either to the cytosol (c-SAS plants) or to the chloroplast (p-SAS plants). In p-SAS plants, the amount of free and conjugated SA was increased more than 20-fold above wild type (WT) level, indicating that SAS is functional in Arabidopsis. P-SAS plants showed a strongly dwarfed phenotype and produced very few seeds. Dwarfism could be caused by the high SA levels per se or, perhaps more likely, by a depletion of the chorismate or isochorismate pools of the chloroplast. Targeting of SAS to the cytosol caused a slight increase in free SA and a significant threefold increase in conjugated SA, probably reflecting limited chorismate availability in this compartment. Although this modest increase in total SA content did not strongly induce the resistance marker PR-1, it resulted nevertheless in enhanced disease resistance towards a virulent isolate of Peronospora parasitica. Increased resistance of c-SAS lines was paralleled with reduced seed production. Taken together, these results illustrate that SAS is a potent tool for the manipulation of SA levels in plants.
Keywords: salicylate synthase; chorismate; metabolic engineering; bifunctional enzyme; disease resistance; Arabidopsis